Dual‐Strategy to Construct Aqueous‐Based Symmetric Supercapacitors with High Volumetric Energy Density. Issue 3 (6th February 2020) - Zhang, Li; Wu, Dandan; Ma, Quanhu; Wang, Gaowei; Liu, Ziqiang; Chang, Meixia; Yan, Xingbin
Abstract: Carbon‐based supercapacitors have been widely used in electric vehicles because of their high‐power density, long cycle life and fast charge/discharge rates. However, low volumetric energy density severely limits their application for miniaturized electronic devices. Here, we have demonstrated a carbon‐based symmetric supercapacitor by using a three‐dimensional porous graphene with high density as the electrode material and a 17 M NaClO4 water‐in‐salt electrolyte with a 2.1 V electrochemical stability window. The device exhibited high specific capacitance (145.3 F cm −3 at 0.5 A g −1 ), excellent rate performance (70.0 % capacitance retention even at 50 A g −1 ), high volumetric energy density (22.3 Wh L −1 at 333.4 W L −1 based on the total mass of active materials) and excellent cycle stability with 99.1 % capacitance retention after 10, 000 cycles at 5 A g −1 . The performance of this device was superior to the most current supercapacitors based on carbon materials. This effective dual‐strategy of simultaneously regulating capacitance and potential window can greatly promote the further development of aqueous carbon‐based supercapacitors. Abstract : Water‐in‐salt : We creatively combined a high‐density three‐dimensional graphene electrode with a high‐concentration NaClO4 aqueous electrolyte to construct a symmetric supercapacitor, which shows high gravimetric and volumetric energy density of 17.5 Wh kg −1 and 22.3 Wh L −1 under 2.1 V electrochemical stabilization window, respectively.